2009
DOI: 10.1111/j.1365-4632.2009.03940.x
|View full text |Cite
|
Sign up to set email alerts
|

Unusual clinical variants of cutaneous leishmaniasis in Sicily

Abstract: The global number of cases of cutaneous leishmaniasis in Sicily has increased in recent years, and such increases can be explained, in part, by the fact that, in this region, sandflies are present during a large part of the year. This is a result of the climatic variation in recent years (increasing temperature and humidity). There has also been an increase in the number of new and rare variants of cutaneous leishmaniasis. A knowledge of the unusual clinical variants of cutaneous leishmaniasis, as well as clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 11 publications
1
30
0
1
Order By: Relevance
“…Previously the specie or the strain of leishmania was understood to be the determining factor for the clinical presentation of leishmaniasis. However,currently it is postulated that the interaction between the host immune response and the strain of the parasite influence the clinical presentation of CL and not only the leishmania's strain [5] In terms of ECL this conjecture is supported by the fact that in all previous reports different species of leishmania were incriminated: L. infantum [7], L. panamensis [5]. In our context, the identification of the leishmania's species is not a routine test.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Previously the specie or the strain of leishmania was understood to be the determining factor for the clinical presentation of leishmaniasis. However,currently it is postulated that the interaction between the host immune response and the strain of the parasite influence the clinical presentation of CL and not only the leishmania's strain [5] In terms of ECL this conjecture is supported by the fact that in all previous reports different species of leishmania were incriminated: L. infantum [7], L. panamensis [5]. In our context, the identification of the leishmania's species is not a routine test.…”
Section: Discussionsupporting
confidence: 53%
“…The reasons for this clinical form are poorly understood, but clinical and experimental evidence indicates that vector, parasite and host factors all influence the evolution and outcomes of the broad clinical spectrum of CL. It has been suggested that as with leprosy ,the various atypical lesions of CL are determined by different types of immune response .The granuloma observed in ECL may be explained by the spread of the parasit in the superficial layer of the papillary dermis and the failure of the immune systeme to control parasit replication [7]. Other factors such as skin fragility due to senility, hormonal changes at menopause and trauma were evoked as facilitating factors of ECL given the predilection location to the face, the predominant affection of elderly females and the antecedent of trauma in some reports [4,6].…”
Section: Discussionmentioning
confidence: 99%
“…This species had been reported previously as the etiological agent of diffuse cutaneous leishmaniasis in an AIDS patient (16), and in three patients with disseminated, erysipeloid and leishmaniasis recidivans cutis (4). This contrasts with numerous reports on atypical cases from the Mediterranean basin (12) and from other countries, including Pakistan (5-7,11,13,17), India (18), Iran (8,9) and Lebanon (19), where the major infective species is L. major. In these publications, the clinical polymorphism of the disease has been related to parasite dependent factors, such as virulence of the species (5,6,8,9,18), the vector (12), and geographical region where infection took place (11,12,18), and to the host, such as lesion localization (5,8) and immune response (5)(6)(7)(8)11,12,18).…”
Section: Discussionmentioning
confidence: 57%
“…It has also been suggested that in other atypical forms, such as erysipeloid leishmaniasis, parasite dissemination in the papillary dermis hinders the ability of the immune system to control the disease (12,21). Since the three patients in this series had numerous amastigotes, it is possible that the host´s deficient immune response, when faced with certain Leishmania species (L. panamensis and L. braziliensis in the New World and L. major in the Old World), allows for parasite replication and dissemination with a clinical pattern different from the typical one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation